1999
DOI: 10.1016/s0014-5793(99)00971-0
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase regulatory protein is essential for the proper subcellular localisation of liver glucokinase

Abstract: Glucokinase (GK), a key enzyme in the glucose homeostatic responses of the liver, changes its intracellular localisation depending on the metabolic status of the cell. Rat liver GK and Xenopus laevis GK, fused to the green fluorescent protein (GFP), concentrated in the nucleus of cultured rat hepatocytes at low glucose and translocated to the cytoplasm at high glucose. Three mutant forms of Xenopus GK with reduced affinity for GK regulatory protein (GKRP) did not concentrate in the hepatocyte nuclei, even at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 26 publications
6
83
2
Order By: Relevance
“…It was reported that the allosteric effectors of GKRP such as F1P and F6P bind GKRP and alter the interaction between GK and GKRP and eventually the GK activity (11,14,16). As xGKRP has been shown to be insensitive to the binding of F6P and F1P (24), we used hGKRP to investigate the molecular mechanism by which effectors of GKRP modulate the GK activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that the allosteric effectors of GKRP such as F1P and F6P bind GKRP and alter the interaction between GK and GKRP and eventually the GK activity (11,14,16). As xGKRP has been shown to be insensitive to the binding of F6P and F1P (24), we used hGKRP to investigate the molecular mechanism by which effectors of GKRP modulate the GK activity.…”
Section: Resultsmentioning
confidence: 99%
“…GKRP is known to be located mainly in hepatocytes with an excess ratio to GK, regulating the allosteric GK in response to glucose concentration (12,14,15). To get some insight into the physiological implications for the role of GKRP, we attempted to investigate the regulatory features of GKRP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunostaining-Cells cultured on 13-mm coverslips were washed in PBS, fixed in 4% paraformaldehyde in PBS (30 min), and washed in PBS (11). They were incubated with NaBH 4 (1 mg/ml, 10 min) and then permeabilized in 0.2% (v/v) Triton X-100 in PBS and blocked with 1% bovine serum albumin/0.02% Triton X-100/PBS.…”
Section: Methodsmentioning
confidence: 99%